Die Inschriften zu den Ludi saeculares Acta ludorum saecularium - Schnegg, Bärbel (De Gruyter, 2020)
The Saecular Games are considered one of the best-testified religious festivals of ancient Rome. The most significant source are two inscriptions, the Acta augustea and the - partially badly damaged - Acta severiana. The volume offers a completely newly constituted Latin text of both inscriptions with translation and detailed commentary. In addition, other important texts to the Ludi saeculares are provided in the original and in translation.